Desain pin hole mempengaruhi kuat rekat geser gigitiruan jembatan adesif Pin hole design affect shear bond strength of adhesive bridge - Edy Machmud; Moh. Dharmautama; Herawati Herawati (Journal of Dentomaxillofacial Science, 2013)
To overcome the failure of adhesive bridge due to release of the adhesive bond cement between teeth and metal,preparation modification was performed with a pin hole in the teeth cingulum. This study aimed to determine the effectof thread on a pin hole to shear strength adhesion of adhesive bridge. Forty maxillary incisors were prepared at theirpalatinal surfaces 0.3 mm thick, and were divided into four treatments (threaded hole+threaded pin, threaded holes+non-threaded pin, non-threaded holes+threaded pin, non-threaded holes+non-threaded pin). Casted-plates made fromnickel chromium alloy were cemented to the palatal surface of the tooth with adhesive cement (Panavia TMF 2.0), andthen adhesion shear strength tested. The test and evaluation of the residual cement on the surface were performed inLaboratory Metallurgy, Department of Engineering ITB. Data were analyzed by one-way ANOVA test (p=0.05).Adhesion shear strength of plate with threaded holes+threaded pin has the highest retention. Residual cement onthreaded hole+threaded pin plates similar to threaded hole+non-threaded pin, but more than any other groups. theconclusions were, the adhesion shear strength depends on the design of pin hole. The wider surface of cementremaining on the plates, the greater adhesion shear strength.